APPLYING THE DISCOVERY LEARNING TO IMPROVE LEARNERS’ READING COMPREHENSION THROUGH ONLINE DICTIONARY APPLICATION - Adetya Norizkyka (Pahlawan, 2020)
Discovery learning approaches, in particular, are designed to engage students in inquiry through which, guided by the teacher and materials, they "discover" the intended content. Still, the tension remains, for example, in moments when students make discoveries other than as intended The choosing of word in dictionary influences the meaning of comprehending the text by the students. In dictionary, there are so many meanings in one word. It based on the context that we have to use to comprehend a text. The discussion starts with the condition of nowadays, there are two kinds of dictionary named printed and online dictionary. These two kinds of dictionary can help the students to improve their comprehension to understand a text. Besides using the dictionary, the students needed to discover the learning process by them in choosing the word showed by the online dictionary to be used in comprehend a certain text. This journal concentrates in improving the comprehension of the text of students’ using online dictionary and discovery learning.